Conversational Implicatures in Advertising Language of Pepsodent Toothpaste Products on Youtube Channel - Izabella Ramadhani Putri (Yayasan Baru Haji Samsudin, 2025)
This study aims to describe the forms or types of conversational implicatures and their functions in utterances found in Pepsodent toothpaste advertisements on YouTube channels. The research uses pragmatic theory as its analytical framework, since pragmatics examines the meaning of utterances within specific communicative contexts. This research is qualitative and descriptive in nature, with data collected using the listening method followed by transcription techniques. Data analysis was conducted using three methods: the matching method with the determining element sorting technique (PUP), the distribution method with the direct element distribution technique (BUL), and descriptive analysis.The results show that various utterances in Pepsodent advertisements contain both general and specific conversational implicatures. These implicatures reflect communication strategies used to capture viewers’ attention, build the product’s image, and convey persuasive messages subtly. Furthermore, each utterance has four main implicature functions: representative/assertive, directive, commissive, and expressive. These functions help viewers understand the implied meanings, increase awareness of product advantages, and motivate specific actions, such as purchasing the product.This study provides important insights into how language is strategically used in promotional media and highlights the significance of pragmatic analysis in revealing implied meanings in advertising communication. The findings can serve as a reference for linguistics researchers, advertising practitioners, and media developers to design more effective and persuasive communication strategies in future marketing campaigns